KEBERHASILAN PELAYANAN STRATEGIS KONSUMEN TOKO RETAIL - Budiono, Gatut L.; Sawitri, Ni Nyoman (Universitas Islam Negeri Raden Intan Lampung, 2016)
Abstract: The research problem originates from previous research done by Yoon et al (2004:395-412). The instruments were re-research in Depok city West Java. It was measuring the effect of organizational support, supervisory support, customer participation, and job satisfaction and employee service quality. This research was to attest the hypothesis and to examine the effect of organizational support, supervisory support, customer participation in the service effort, job satisfaction and employee service quality.There was significant effect of organizational support, supervisory support, customer participation in service effort, job satisfaction. For future research, what factors are affecting to the service effort and job satisfaction, beside organization support, supervisory support, customer participation, and what factors affecting to the employee service quality, beside service effort, job satisfaction.